2016
DOI: 10.3233/jad-150652
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model

Abstract: Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 76 publications
7
104
0
2
Order By: Relevance
“…We have previously postulated that in the case of aMCI subjects, these cells respond to some still unidentified challenge that may originate from chronic viral, bacterial, or fungal infections. The recent demonstration that beta amyloid peptides, the most important component of the characteristic amyloid plaques in AD, possess antimicrobial properties (1214) is consistent with this notion. Overall, these observations have raised the level of interest in immune changes associated with the development and progression of AD (9).…”
Section: Introductionsupporting
confidence: 53%
“…We have previously postulated that in the case of aMCI subjects, these cells respond to some still unidentified challenge that may originate from chronic viral, bacterial, or fungal infections. The recent demonstration that beta amyloid peptides, the most important component of the characteristic amyloid plaques in AD, possess antimicrobial properties (1214) is consistent with this notion. Overall, these observations have raised the level of interest in immune changes associated with the development and progression of AD (9).…”
Section: Introductionsupporting
confidence: 53%
“…This suggests Aβ binding of viral glycoproteins may not be the sole pathway mediating targeting of herpesviridae . Consistent with alternative/complementary herpes targeting pathways, Bourgade et al ., 2016 report HSV1 inhibition mediated by binding of a proximal region of gB with high sequence homology to Aβ (Bourgade et al, 2016). …”
Section: Resultsmentioning
confidence: 67%
“…However, mounting data suggest this long-standing model for Aβ pathogenesis requires revision. Recent findings have identified Aβ as an antimicrobial peptide (AMP), and suggest Aβ deposition may be a protective innate immune response to infection (Bourgade et al, 2015; Bourgade et al, 2016; Kumar et al, 2016; Soscia et al, 2010; White et al, 2014). A physiological role for Aβ as an AMP is also consistent with the peptide’s remarkably high sequence conservation across multiple phyla - the human Aβ sequence is at least 400 million years old and is found in 60–70 % of vertebrate species (Luna et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that Aβ protects against C. albicans infection in glial cells in vitro and in nematodes in vivo [69]. In addition, Aβ inhibits HSV-1 viral replication in vitro, and protects mice from Salmonella Typhimurium infection in vivo, which led the authors of both studies to conclude that Aβ may have a previously unknown protective role in innate immunity, along with the pathogenic characteristics that are extremely well studied [69, 70]. …”
Section: Reviewmentioning
confidence: 99%